2022
DOI: 10.3390/diagnostics12051231
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Conspicuity of Liver Metastases in Virtual Monochromatic Imaging Reconstructions on a Novel Photon-Counting Detector CT—Effect of keV Settings and BMI

Abstract: In dual-energy CT datasets, the conspicuity of liver metastases can be enhanced by virtual monoenergetic imaging (VMI) reconstructions at low keV levels. Our study investigated whether this effect can be reproduced in photon-counting detector CT (PCD-CT) datasets. We analyzed 100 patients with liver metastases who had undergone contrast-enhanced CT of the abdomen on a PCD-CT (n = 50) or energy-integrating detector CT (EID-CT, single-energy mode, n = 50). PCD-VMI-reconstructions were performed at various keV le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The authors observed significant dose reduction (mean CTDI vol of 12.00 mGy for PCD-CT vs 16.05 mGy for DSCT) while maintaining similar or even improved image quality. The benefits of PCD-CT in the evaluation of obese oncologic patients have also been described elsewhere 34 …”
Section: Benefits Of Photon-counting Detector Ct and Their Clinical T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors observed significant dose reduction (mean CTDI vol of 12.00 mGy for PCD-CT vs 16.05 mGy for DSCT) while maintaining similar or even improved image quality. The benefits of PCD-CT in the evaluation of obese oncologic patients have also been described elsewhere 34 …”
Section: Benefits Of Photon-counting Detector Ct and Their Clinical T...mentioning
confidence: 99%
“…Several clinical studies have investigated the image quality of VMIs from PCD-CT, their CNR, and the associated radiation dose to the patient compared with EID-CT 61 . A cohort of 50 oncologic patients with liver metastases scanned with a PCD-CT at 120 kV was compared with a matched group of 50 patients scanned with an EID-CT with automatic tube voltage selection, proposing 100 kV for most of the scans 34 . Compared with the polychromatic images from EID-CT, the VMIs from PCD-CT demonstrated reduced image noise at 70 keV and consistently higher CNR in the 40–70 keV range at a similar radiation dose (CTDI vol of 6.7 mGy for PCD-CT vs 6.4 mGy for EID-CT).…”
Section: Benefits Of Photon-counting Detector Ct and Their Clinical T...mentioning
confidence: 99%
“…Therefore, it was not possible to conclude whether the CNR of the PCD-system will also be superior at lower iodine concentrations found in the venous or late enhancement phase. A paper by Bette et al investigated the enhancement of liver metastases and demonstrated the improvements in the use of VMI from PCD-CT in clinical use [ 25 ]. They concluded that CNR was preserved across a broad body mass index (BMI).…”
Section: Discussionmentioning
confidence: 99%
“…The PCD technology has several major benefits over existing energy-integrating detectors, such as removal of electronic noise, increased iodine CNR, higher spatial resolution, and reduced radiation dose 12 . For example, PCD-CT image quality was better compared with EID-CT in terms of reduced beam hardening artifacts and image noise 13,14 . In addition, the PCD-CT routinely enables multienergy CT by allocating photons into multiple energy bins, enabling creation of VMIs.…”
mentioning
confidence: 99%
“…12 For example, PCD-CT image quality was better compared with EID-CT in terms of reduced beam hardening artifacts and image noise. 13,14 In addition, the PCD-CT routinely enables multienergy CT by allocating photons into multiple energy bins, enabling creation of VMIs. The optimal photon energy of VMIs varies depending on the clinical task; 50 keV was shown to be an optimum photon energy for improved CNR and detectability of low-contrast lesions in abdominal CT compared with single-energy CT in phantoms 15 and for viewing contrast-enhanced abdominal PCD-CT considering vascular and organ CNR and subjective image quality.…”
mentioning
confidence: 99%